Assessment of Common Maternal Risk Factors in Fetal Malnutrition - Poudel, Anshu; Bhatta, Nisha K; Regmi, Mohan Chandra; Shah, Lokraj; Paudel, Rajan (Birat Journal of Health Sciences, 2021)
Introduction: Nutritional assessment of the newborn gives the reflection of the growth process in the intrauterine period. The Clinical Assessment of Fetal Nutritional Status score (CAN score) method is only the method to assess the fetal malnutrition which includes the clinical observation for the presence of the sign of malnutrition in newborns. Since the fetal growth is related to availability of intrauterine nutrition and placental function, there may be several maternal factors associated with the fetal malnutrition.Objectives: The main objective of the study was to determine the prevalance of Fetal Malnutrition in term newborns and the role of maternal factors in the etiology of fetal malnutrition (FM) in the Neonatal and Maternity Units of B.P Koirala Institute of Health Sciences, Dharan.Methodology: This was a hospital based observational cross sectional study of consecutive, singleton, term live babies delivered between September 2019 to March 2020. Fetal malnutrition was diagnosed using Clinical Assessment of Fetal Nutritional Status score (CAN score) developed by Metcoff. The maternal history was obtained from the mother which included age, parity, socioeconomic class, pre pregnancy weight, number of antenatal care during pregnancy, history of maternal illness and drugs taken during pregnancy. Nutritional status of the mother was determined using weight, height, mid arm circumference (MAC) and the body mass index (BMI). Collected data was entered in Microsoft excel 2010 and converted it into SPSS 23 version software, for statistical analysis.Results: Of the 400 studied newborns, 73 [18%] had FM. The prevalence of teenage pregnancy, primiparity, lower maternal mid arm circumference and vegetarian diets were higher in the mothers of the babies who had suffered fetal malnutrition than the mothers of the babies without FM (p value